Dampak Harga CPO, Pajak Ekspor, dan Konsumsi Minyak Global Terhadap Ekspor CPO Indonesia (Jurnal Ekonomi Pembangunan Widya Mandira, 2025)
This study explores the impact of Crude Palm Oil (CPO) prices, export taxes, and global oil consumption on Indonesian CPO exports using a documentary analysis methodology. The primary focus of this research is to understand how these variables affect the volume of Indonesian CPO exports by relying on available secondary data and documents. The analyzed documents include international trade reports, commodity price statistics publications, export tax policy data, and global oil consumption reports. This methodology involves collecting and evaluating relevant documents from various sources, including government agencies, international organizations, and industry reports. The analysis was conducted by categorizing and coding relevant information from these documents to identify patterns and relationships among the studied variables. The results of the documentary analysis indicate that CPO prices have a positive and significant impact on Indonesian CPO exports, consistent with global commodity price trends. Export taxes have been shown to have a significant negative impact, indicating that tax policies can substantially affect export volumes. Although global oil consumption is related to global market dynamics, it does not show a significant impact on Indonesian CPO exports within the context of the analyzed data. This study concludes that CPO prices and export taxes are key factors affecting Indonesian CPO exports, while global oil consumption has a more marginal effect. These findings provide insights for policymakers and industry stakeholders to consider these factors when formulating trade and tax policies to enhance the competitiveness of Indonesian CPO exports in the global market.
Keywords: Crude Palm Oil, Export Taxes, Global Oil Consumption, Exports, Indonesia